Analisis Kesesuaian Perangkat Pelaksanaan Pembelajaran dengan Tuntutan Pembelajaran Abad 21 - Mukarramah Mukarramah*; Abdul Gani; Sri Winarni (Program Studi Magister Pendidikan IPA Program Pascasarjana Universitas Syiah Kuala, 2021)
RPP is one of the things that determine the success of the learning process carried out by the teacher. This study aims to describe the suitability of the RPP material for the periodic system of elements with the demands of 21st century learning. This study uses a qualitative approach with a descriptive type of research. The data in this study are the RPP components contained in the PPG RPP which are downloaded on the Ministry of Education and Culture RI teacher sharing website and the chemistry teacher RPP at several schools in Banda Aceh. Data collection is done by using documentation technique, while data analysis is done by qualitative descriptive technique which includes data reduction, data presentation, and drawing conclusions. The results showed that the PPG lesson plans contained on the teacher sharing website and the lesson plans developed by teachers at several schools in Banda Aceh were in accordance with the demands of 21st century learning. All lesson plans had integrated the elements required in 21st century learning, namely strengthening character education (PPK), Literacy, HOTS, and 4C (communication, collaboration, creativity, critical thinking). The elements of KDP that have been integrated into the RPP include religious values, independence, mutual cooperation, nationalism, and integrity. Next, the elements of literacy that are integrated are basic literacy, media literacy, technological literacy, and visual literacy. Furthermore, the HOTS element in lesson plans is shown by the use of operational verbs to analyze, evaluate, and compare several components of lesson plans, such as GPA and learning objectives. Then, the 4C component in the lesson plans has been demonstrated through learning activities in the form of discussions, presentations, and group assignments. Thus, it can be concluded that the lesson plans designed by teachers are in accordance with the demands of 21st century learning